2018
DOI: 10.1002/tox.22688
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effect of Turnera diffusa against testicular toxicity induced by fenitrothion and/or hexavalent chromium in rats

Abstract: Oxidative stress and increased production of reactive oxygen species have been implicated in pesticides and heavy metals toxicity. The objective of this study was to investigate the efficacy of Turnera diffusa Willd (damiana) on counteracting fenitrothion (FNT) and/or potassium dichromate (CrVI)-induced testicular toxicity and oxidative injury in rats. FNT and/or CrVI intoxicated animals revealed a significant increase in thiobarbituric acid reactive substances and hydrogen peroxide levels. While, reduced glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 80 publications
2
15
0
Order By: Relevance
“…Zari and Al-Attar (2011) showed that treatment of male rats with CBZ resulted in severe damage and completely absences of spermatogonia, primary spermatocytes, secondary spermatocytes, spermatids and spermatozoa and losses of the spermatogenesis process. Moreover, adverse reproductive effects attributed to pesticides, including their effect on fertility, have also been well established in various experimental studies ( Hassan and Meligi, 2017 , El-Demerdash et al, 2019 , Ghorbani Taherdehi et al, 2019 , Osama et al, 2019 )…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Zari and Al-Attar (2011) showed that treatment of male rats with CBZ resulted in severe damage and completely absences of spermatogonia, primary spermatocytes, secondary spermatocytes, spermatids and spermatozoa and losses of the spermatogenesis process. Moreover, adverse reproductive effects attributed to pesticides, including their effect on fertility, have also been well established in various experimental studies ( Hassan and Meligi, 2017 , El-Demerdash et al, 2019 , Ghorbani Taherdehi et al, 2019 , Osama et al, 2019 )…”
Section: Discussionmentioning
confidence: 96%
“…Under normal physiological conditions, cellular ROS generation is counterbalanced by the action of antioxidant enzymes and other redox molecules. Oxidative stress is potentially harmful to cells, and ROS are produced as a reaction to pesticide toxicity ( El-Demerdash et al, 2019 ). SOD and CAT are important antioxidant enzymes in organisms, which can remove superoxide free radicals and prevent the production of hydroxyl free radical.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this wastewater needs to be investigated, and some artificial methods should be used to help impart crop yield and productivity. Among various heavy metals, chromium (Cr) is an extremely noxious metal to living organisms and has negative effects reported in humans [14], animals [15], plants [16] and micro-organisms [17]. Cr is a major toxic element discharged into the environment through various industries, such as tanning, electroplating, manufacturing of pigments, production of nuclear weapons and corrosion control [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the supplementation with vitamin C appears to prevent chromium (VI)-induced OS [ 107 ]. The conclusions obtained by Aruldhas M. and colleagues through their study in monkeys exposed to chromium (VI) were supported by several other animal studies [ 108 , 109 , 110 , 111 , 112 ]. So extensive studies are not possible to be performed in humans.…”
Section: Redox Balance In Male Reproductive Tissues and Chromium Compoundsmentioning
confidence: 52%
“…Further, it decreases the activity of antioxidant enzymes and the concentration of non-enzymatic antioxidants, both in testis and seminal fluid. The severe oxidative state promoted by chromium (VI) ultimately leads to a decrease in sperm quality and male fertility potential [ 108 , 109 , 110 , 111 , 112 ]. Nevertheless, it appears that the harmful effects of chromium (VI) on the male reproductive system can be reversed either through time (in a chromium (VI)-free environment), or by supplementing males with an antioxidant compound, such as vitamin C [ 107 ].…”
Section: Discussionmentioning
confidence: 99%